Roads and Ruins : The Symbolic Landscape of Fascist Rome - Baxa, Paul, 1968- (Book collections on Project MUSE., 2010)
Drawing on a wide variety of sources, including war diaries, memoirs, paintings, films, and government archives, Roads and Ruins is a richly textured study that offers an original perspective on a well known story.